Peripheric smell regions in patients with temporal and frontal lobe epilepsies: An MRI evaluation. (October 2021) - Inal, Mikail; Bayar Muluk, Nuray; Asal, Neşe; Alpua, Murat
Highlights: Temporal and frontal epilepsy maybe related to decrease in OB volume. Temporal and frontal epilepsy may cause olfactory impairment. Olfactory deficit maybe related to central epileptic focus. Olfactory impairment may help early diagnosis of the epilepsy. Abstract: Objectives: We investigated peripheric smell regions of olfactory bulb (OB) volume and olfactory sulcus (OS) depth in temporal and frontal lobe epilepsy patients by cranial magnetic resonance imaging (MRI). Methods: In this retrospective study, cranial MRI images of 150 adult patients were included. Group 1 was consisted of 50 adult patients with temporal lobe epilepsy (TLE). Group 2 was consisted of 50 adult patients with frontal lobe epilepsy (FLE). The control group (Group 3) was consisted of 50 healthy subjects without epilepsy. OB volume and OS depth were measured in all groups. Results: OB volumes of the temporal and frontal epilepsy groups were significantly lower than those of the control group (padjusted  < 0.0175). However, OS depths were not different between groups 1–3 (p > 0.05). In the temporal and frontal epilepsy groups, there were positive correlations between OB volumes; OS depths; left OB volume and bilateral OS depths p < 0.05). There were no significant correlations between OB volume and OS depth; and age and gender of the epilepsy group (p > 0.05). Conclusion: We concluded that temporal and frontal epilepsy maybe related to decrease in OB volume and may cause olfactory impairment. Olfactory deficit maybe related to central epileptic focus. Therefore, early diagnosis and appropriate treatment of epilepsy are important to prevent olfactory impairment.